2016 IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS) 2016
DOI: 10.1109/iros.2016.7759057
|View full text |Cite
|
Sign up to set email alerts
|

Estimating object hardness with a GelSight touch sensor

Abstract: Abstract-Hardness sensing is a valuable capability for a robot touch sensor. We describe a novel method of hardness sensing that does not require accurate control of contact conditions. A GelSight sensor is a tactile sensor that provides high resolution tactile images, which enables a robot to infer object properties such as geometry and fine texture, as well as contact force and slip conditions. The sensor is pressed on silicone samples by a human or a robot and we measure the sample hardness only with data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 20 publications
0
42
0
1
Order By: Relevance
“…For example, contact geometry in pixel space could be used in combination with knowledge of grasping force and gel material properties to infer 3D local object geometry. If markers are placed on the gel surface, marker flow can be used to estimate object hardness [20] or shear forces [21]. These quantities, as well as the sensor's calibrated image output, can be used directly in model-based or learningbased approaches to robot grasping and manipulation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, contact geometry in pixel space could be used in combination with knowledge of grasping force and gel material properties to infer 3D local object geometry. If markers are placed on the gel surface, marker flow can be used to estimate object hardness [20] or shear forces [21]. These quantities, as well as the sensor's calibrated image output, can be used directly in model-based or learningbased approaches to robot grasping and manipulation.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous work [5], we showed that GelSight can accurately estimate the hardness of a set of hemispherical silicone samples under loosely controlled contact conditions. As in this work, we asked a human tester and an open-loop robot to press on samples, and developed a model to predict the hardness according to both the changing brightness in the GelSight image and the displacement field of the surface markers.…”
Section: B Hardness Measurementmentioning
confidence: 99%
“…We take a sequence of images during the contact procedure as our input signal. showed in our previous work [5] that these physical changes could be measured using simple image cues: namely, changes in intensity and motion of the black markers embedded in the gel. Figure 2 shows an example.…”
Section: Introductionmentioning
confidence: 96%
“…In [77] a robot leg equipped with an accelerometer is employed to actively knock on object surfaces and by analysing the sensor data, the hardness, elasticity and stiffness of the object can be revealed. In recent works [78], [79], the hardness of objects can also be estimated by processing the tactile image sequences from a GelSight sensor. In [80], multiple computational algorithms are applied to classify various materials based on mechanical impedances using tactile data and it is found that SVM performs best.…”
Section: B Object Stiffness Based Tactile Materials Recognitionmentioning
confidence: 99%